2021
DOI: 10.1016/s0140-6736(21)01164-8
|View full text |Cite
|
Sign up to set email alerts
|

Participation of people living with disabilities in physical activity: a global perspective

Abstract: wrtin qinisD uthleen e nd vn der loegD ridde nd posterD ghrlie nd viD fyron nd wfrideD ghristopher f nd xgD uwok nd rttD wihel nd hirzipourD gelin r nd mithD frett nd ¡ squezD risill w nd rethD qregory @PHPIA 9rtiiption of people living with disilities in physil tivityX glol perspetiveF9D he lnetFD QWV @IHPWVAF ppF RRQERSSF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
219
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(228 citation statements)
references
References 89 publications
3
219
0
6
Order By: Relevance
“…The findings from this study were consistent with other studies that demonstrated a reduction in PA and increase in SB during the pandemic in CYWD [ 27 , 28 , 29 , 30 ]. Traditional barriers to healthy movement and play that CYWD experience may be categorized into individual factors (e.g., fear, pain), sociocultural factors (e.g., family and friend support), environmental factors (e.g., built environment, weather) and/or systemic factors (e.g., inaccessibility facilities) [ 42 , 44 ]. During the COVID-19 pandemic, participation in PA and play has been further challenged and barriers have worsened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study were consistent with other studies that demonstrated a reduction in PA and increase in SB during the pandemic in CYWD [ 27 , 28 , 29 , 30 ]. Traditional barriers to healthy movement and play that CYWD experience may be categorized into individual factors (e.g., fear, pain), sociocultural factors (e.g., family and friend support), environmental factors (e.g., built environment, weather) and/or systemic factors (e.g., inaccessibility facilities) [ 42 , 44 ]. During the COVID-19 pandemic, participation in PA and play has been further challenged and barriers have worsened.…”
Section: Discussionmentioning
confidence: 99%
“…Parental support has been shown to be a key determinant of healthy movement and play behaviours in CYWD [ 42 , 43 , 44 ]. Parental support may include tangible support (e.g., co-participation in healthy behaviours, providing transportation to PA programs or services) or intangible support (e.g., encouraging healthy behaviours or discouraging unhealthy behaviours) [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3 new Lancet series papers on physical activity [1][2][3] build on the evidence presented in 2 previous series 4,5 that underlined the pandemic magnitude of physical inactivity, its health, social, environmental and economic global consequences, and the urgency to take immediate multisectoral actions to make active living an affordable and accessible choice for all population groups. These messages were based on unquestionable evidence of the beneficial effects of physical activity on virtually every system of the body, supporting it as a "best buy in public health."…”
mentioning
confidence: 99%
“…Children and adolescents, the elderly, and people with disabilities should be specifically targeted for intervention strategies, given the high prevalence of inactivity in these groups and potential for numerous physical and mental health benefits. 2,3 The COVID-19 pandemic continues to advance in many countries, and it will likely take many months before most of the world's population is vaccinated. Urgent action is needed to tackle the collision of the inactivity, NCD, and COVID-19 pandemics (also known as a syndemic), including effective public health strategies to promote physical activity as a means of reducing health inequities, morbidity, and mortality from COVID-19 and NCDs.…”
mentioning
confidence: 99%
“…Measuring BCT delivery and receipt in the context of PA counseling for people with physical disabilities is particularly important and interesting to explore, because PA participation is generally low in people with disabilities (Martin Ginis et al, 2021) and they face so many different barriers to PA on different levels (e.g., interpersonal, intrapersonal, organization, community, policy; Martin Ginis et al, 2016; Martin Ginis et al, 2021). As such, a variety of BCTs are expected to be needed to support this population to engage in PA.…”
Section: Introductionmentioning
confidence: 99%